(untitled) (Fiep Bulletin - online, 2014)
Life style has been a central worry in studies related to obesity in the past years. Thus, the aim of this research was to perform an analysis among physical fitness indicators related to students’ health in private schools in Maringá-PR-Brazil. The sample used was formed with 1630 students, 780 female and 850 male, aged between 7 and 17 years-old, who were attending the classes. The data collection was done between August and September, 2003, during Physical Education classes, by the research authors, Physical Education teachers and trainees of Physical Education university course. In order to analyse the patterns, the Physical Best (AAHPERD, 1988) health criteria were used; to determine overweigh and obese people cut values to Corporal Mass Index (CMI) were used, suggested by Dietz e col. (2000). The statistical analysis comprehended the figures calculation in quartiles. The produced results were presented with frequency and percentage of the students who fulfilled the criteria to every quartile. The main results of the present study refer to low number of students who fulfilled the criteria proposed by Physical Best, concerning cardiac breathing fitness and muscles strength/resistance in all ages, having only the flexibility aspect reached nearly 50% of the students fulfilling the criteria. As central conclusive aspects, it is possible to verify that cardiac breathing fitness and muscles strength/resistance showed, in every quartile, only a small percentage of students who fulfilled the health criteria, mainly in p75. It is important to observe that quartile p75 represents the cut values to overweigh people suggested by Cole et al. (2000). The reached results to cardiac breathing fitness and muscles strength/resistance, as well as the figures increase concerning overweigh and obesity maintenance among our students may indicate a decrease in occupational physical activity, so as a lack of physical exercises in our society.